PERBANDINGAN KADAR OKSIGEN TERLARUT ANTARA AIR PDAM DENGAN AIR SUMUR - HAYATI, MALA (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
PERBANDINGAN KADAR OKSIGEN TERLARUT ANTARA AIR PDAM DENGAN AIR SUMUR Mala Hayati, S.TP., M.Kes.Prodi D3 Analis Kesehatan UM Surabaya AbstractWater is a basic necessity for life. Fulfillment of the city water comes from well water and processed water  PDAM. Water PDAM is safe for consumption is used chlorine as a disinfectant. But sometimes the excessive use of water PDAM that often smells of chlorine. So before using our society, used to be stored in the reservoir with chlorine hope has evaporated. Based on this background research conducted this experiment to determine the chlorine content of the water from the PDAM before and after treatment for 24 hours in water reservoir. In this experimental study, using 16 water samples taken in the area PDAM Bratang Ngagel Rejo Kecamatan  Wonokromo Surabaya. The samples were divided into two groups analyzed chlorine residual levels before and after in the tank for 24 hours using standard methods based ortholuidin read color expressed in units of mg / 1. The result showed that the levels of residual chlorine in PDAM water before water reservoir average was 0.20 mg / 1 and levels of residual chlorine in the tank after 24 hours the average is 0.15 mg / 1. So the conclusion is no significant difference in the independent t test was 4.12538 t value is greater than the table t value of 2.13 with alpha (a) .0,05.Keyword : Chlorine, Disinfectant